Multimedia streaming over wireless communication network - Zheng, Qin Hao. (2010)
This report documents the analysis required and the results obtained to fulfill the requirements of the Final Year Project (FYP) A3047-091: Multimedia Streaming Over Wireless Communication Network in the academic year 2009/2010. The purpose of this project includes streaming JPEG 2000 images from the server to the client using JPEG 2000 Internet Protocol as the application-layer protocol and progressively decodes the received images into its equivalent 3D model. The implementation of a client-server application streaming 2D images will be done first before carrying out the steps to decode the images. For the 2D streaming application, the client side will view images that progressively get better as more data is received. As for streaming of 3D model, it will be based on the received JPEG 2000 images and perform decoding. The report will first begin by discussing the theories and concepts involved to know more about the client-server system and its interaction. It gives an understanding of the tasks that are performed by the end-systems and the network. The second part of the report will cover the development process of the client-server applications. The user interface of the client and the server will be presented and the features of it will be illustrated.